Duodenal ileus caused by a cage magnet in a Fleckvieh cow - Huber, Lisa; Feist, Melanie; Knubben-Schweizer, Gabriela; Trefz, Florian M. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2024)
The present report aims to describe the case of a duodenal obstruction ileus in a dairy cow that was caused by a cage magnet. The 4.7-year-old German Fleckvieh cow was hospitalized because of symptoms of intestinal obstruction such as anorexia, noticeable drop in milk yield, reduced defecation, dehydration and positive percussion and swinging auscultation in a circumscribed area cranial of the right flank over the last 2 ribs. Six months as well as 3 days prior to hospitalization the cow had already been treated for signs of hardware disease, which included administration of a cage magnet.After the initial clinical diagnostic procedure on hospital admission, a diagnostic laparotomy in the right paralumbar fossa was performed to identify the cause of the ileus. The cranial part of the duodenum was markedly dilated, and a solid foreign body was found obstructing the intestine immediately aboral to the duodenal sigmoid flexure. This was identified as a cage magnet, which was massaged in retrograde direction into the pyloric antrum and removed via abomasotomy. The cow recovered from surgical intervention and was discharged from the hospital 6 days later.The present report describes an unusual complication of cage magnet administration, which is a standard veterinary procedure and generally considered a safe treatment option in cows with clinical signs of acute traumatic reticuloperitonitis.
Keywords: Small intestinal ileus; hardware disease; cattle; abomasotomy